OVARIAN GOITER AS A RARE CAUSE OF HYPERTHYROIDISM - Frysak, Z. (Acta Endocrinol (Buchar), 2016)
INTRODUCTION: Thyroid tissue ectopically located in the ovary can be reported accidentally after adnexectomy, but as a primary cause of hyperthyroidism this diagnosis is rare. The clinical search for a functional ectopic thyroid tissue requires intense clinical focus and a multidisciplinary approach. CASE DESCRIPTION: This case report demonstrates a patient with a history of Graves’ disease who had undergone thyroidectomy combined with postoperative (131)I radioablation. Despite the previous treatment, she developed an outburst of hyperthyroidism ten years later. Only very close follow-up enabled us to disclose the right condition. The ovarian source of thyroid hormone production was removed by laparoscopic adnexectomy and a right sided benign ovarian struma was confirmed. CONCLUSION: Most patients treated by thyroidectomy and radioiodine do not require extended periods of follow-up or postoperative investigations, but when the clinical or laboratory signs change, clinicians should be prepared to perform the necessary re-evaluation in order to provide the best care.